Vpliv krožkov kakovosti na rezultate kazalnikov kakovosti v Kliničnem oddelku za pljučne bolezni in alergijo Golnik - Kadivec, Saša (Obzornik zdravstvene nege, 2007)
In health care, quality circles are often referred to as a method for achieving satisfaction of the staff and patients. All participants acquire newknowledge and become better equipped for carrying out the work process. Theobject of the present empirical analysis was to ascertain the efficiency ofa model of a quality circle on the results of certain specific quality indicators - pressure sores, falls, privacy and information delivery. The method was evaluated at the University Clinic of Respiratory and Allergic Diseases. The results revealed that quality circles help achieve better quality in certain areas which were assessed by means of quality indicators.
Keywords: ankete; Bolnik, zdravstveni tim; Bolniški oddelki; Hospital Departments; Kakovost, zagotavljanje zdravstvenega varstva; krožki za kakovost; kvaliteta; Negovalne službe bolnišnične; Nursing Service, Hospital; Patient Care Team; Quality Assurance, Health Care; Questionnaires; timsko delo; zdravstvena nega; zdravstvene službe